Seed Storage Protein Profiles in Cultivars of Capsicum annuum L. - S. Subba Tata, O. Aniel Kumar, T. Rupavati (Recent Research in Science and Technology, 2010)
SDS-PAGE protein profile patterns were studied from seed material of 10 cultivars of C. annuum L. A total of 15 protein polypeptide bands with molecular weights ranging from 22.4 to 80.8kD were recorded. On the basis of seed protein banding nature three varieties could be identified clearly viz., (CA2, CA4 and CA5). Among the varieties CA9 manifested maximum (9) number of protein bands. The greatest similarity (100%) was observed between CA6 and CA7, while the lowest (40%) was noted between (CA3-CA6), (CA3-CA7) and (CA3-CA10). The UPGMA dendrogram represented low genetic diversity. The study revealed that large intra-specific differences were not found in the cultivars, but presence of considerable variations in protein profiles of the cultivars suggested that these selected varieties can be a good source for crop improvement through hybridization programs.